The Evaluation of Protein C Activity and Some Inflammatory Markers in Synovia of Patients Undergoing Total Knee Arthroplasty - (:unkn) unknown (AVES YAYINCILIK, 2010)
Objective: Total knee arthroplasty (TKA) is a major risk factor for thrombosis in patients over 40 years of age and this risk persists for several weeks after the surgery. Since inflammatory mechanisms affect coagulation and the natural anticoagulant system, we aimed to investigate protein C activities and inflammatory markers in patients undergoing TKA surgery. Material and Methods: We included 20 osteoarthritis patients and 20 healthy controls. Protein C activity and tumor necrosis factor-alpha (TNF-alpha) levels in plasma and synovia were evaluated by ELISA technique. Results: In the patient group, protein C activities decreased and TNF-alpha levels increased significantly both in synovia and plasma when compared with the controls. Erythrocyte sedimentation rate of the patient group was found to be significantly elevated in comparison to the controls. On the other hand, serum C reactive protein values increased insignificantly when compared to controls. Conclusion: The decreased activity of protein C and increased levels of inflammatory markers in preoperative plasma and synovia of the patient group may enhance the risk for developing thrombosis.
Keywords: Protein C; hypercoagulability; inflammation; knee arthroplasty; NECROSIS-FACTOR-ALPHA; PERIPHERAL-BLOOD MONOCYTES; RHEUMATOID-ARTHRITIS; PROSTHETIC INFECTION; NEUTROPHIL ELASTASE; REACTIVE PROTEIN; TNF-ALPHA; OSTEOARTHRITIS; COAGULATION; REPLACEMENT